2019
DOI: 10.1093/chromsci/bmz067
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of HPLC and HPTLC Methods for Therapeutic Drug Monitoring of Capecitabine in Colorectal Cancer Patients

Abstract: Capecitabine is a prodrug of 5-fluorouracil, employed as a monotherapy or combination chemotherapy agent for treatment of colorectal cancer. Combination therapy of capecitabine consists of oxaliplatin, and hence, it becomes essential to determine that co-administration does not affect its metabolism. High-performance liquid chromatography and high-performance thin-layer chromatography methods were developed and validated to determine the plasma concentration of capecitabine. In this study, blood samples from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…At present, treatment for CRC mainly consists of surgery supplemented by chemotherapy (5-fluorouracil, oxaliplatin, irinotecan and capecitabine), which can achieve satisfactory therapeutic effects ( 7 9 ). However, a lack of effective treatment methods remain for patients with advanced-stage CRC tumors ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, treatment for CRC mainly consists of surgery supplemented by chemotherapy (5-fluorouracil, oxaliplatin, irinotecan and capecitabine), which can achieve satisfactory therapeutic effects ( 7 9 ). However, a lack of effective treatment methods remain for patients with advanced-stage CRC tumors ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…To increase the therapeutic efficacy of chemotherapy in colorectal cancer, the search for downstream effectors is required. In particular, capecitabine is typically administered as a combinational chemotherapy (with surgery) or as a monotherapy for CRC treatment ( 9 ). It preferentially generates 5-flurouracil (5-FU) which represents a well-established treatment method ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to further verify the implementation of the protein precipitation method using the antineoplastic agent capecitabine and its first metabolite, 5′-deoxy-5-fluorocytidine (5′-DFCR). In this work, the qualitative and quantitative composition of each biological specimen was accurately assessed using high-performance liquid chromatography (HPLC) with ultraviolet (UV) detection (Thorat, Chikhale, Tajne, 2019;Vijaya Jyothi et al, 2018;Hassanlou et al, 2016;Piórkowska et al, 2014;Komarov et al, 2014;Farkouh et al, 2010;Zufı á, Aldaz, Giráldez, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have reported a relationship between drug exposure, toxicity and efficacy (8). In previous reports, the response rate was significantly improved and adverse events were reduced for patients who underwent TDM-based 5-FU dose adjustment compared with patients treated with conventional 5-FU administration (9)(10)(11)(12). Appropriate adjustment of the 5-FU blood concentration can improve both the safety and efficacy of treatment.…”
mentioning
confidence: 99%